Dampak Keberadaan Universitas Islam Negeri Raden Intan Lampung Terhadap Kondisi Ekonomi di Kecamatan Sukarame, Kota Bandar Lampung - Andrean, Alvin; Rahman, Yudha (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2024)
Regional development is an effort made to encourage economic development in achieving prosperity. Welfare is influenced through supply and demand. One of the supply and demand is the existence of educational facilities. Educational facilities are able to provide positive externalities. The education facility in question is the UIN RIL college located in Sukarame District, Bandar Lampung City. Before changing its status to UIN RIL, the existence of the campus had not affected the surrounding economic activities. However, since the increase in status from 2017 to 2022, slowly there have been many developments such as the conversion of land that was previously empty land such as rice fields and shrubs to turned into built-up land such as stalls, grocery stores, photocopies, and so on. This study aims to determine the impact of the existence of UIN RIL on the economic conditions of the people in Sukarame District. This research was conducted by considering two conditions, namely the conditions in 2017 before the increase in status and the current conditions after the existence of UIN RIL until now, namely 2022. This research uses a quantitative deductive approach that is oriented based on variables obtained from the literature review. Data collection techniques using questionnaires and observation. The results showed that the existence of UIN RIL had positive and negative impacts on economic conditions. These positive impacts include increasing employment opportunities, increasing basic and additional income, and increasing asset ownership. While the negative impact is the increase in the amount of public spending. This study also identified the level of impact through scalogram analysis which resulted in Sukarame and Way Dadi Sub-Districts being areas with the highest economic impact due to the existence of UIN RIL.